Characteristics of adolescent boys using protein supplements : diet, lifestyle and health : HLÍF : health and lifestyle in high-school - Unnur Björk Arnfjörð 1976- (2012)
Background: Icelandic diet has always been rich in proteins. Protein supplements are among the most commonly used ergogenic aids and their popularity has been increasing in recent years. The aim of this study was to examine their use among 18 years old high-school boys in Reykjavík, in accordance with their dietary, lifestyle and health. Methods: A cross-sectional study on health and lifestyle of 18-year olds (n=137 boys) was undertaken in three high-schools in Reykjavik. Data consisted of lifestyle- and food frequency questionnaires, 24-h-dietary recalls, graded treadmill test for fitness (VO2max), anthropometric measurements along with Dual-energy X-ray absorptiometry scan (DXA), blood samples from fasting serum levels of triglycerides, total cholesterol (TC), Low-density lipoprotein (LDL), High-density lipoprotein (HDL), insulin, glucose and C-reactive protein (CRP) as well as resting blood pressure. Participants were divided into three groups based on the answers in the question: “How often do you consume protein bars, -powder or –drinks“ i.e. protein consumers (PC) using protein supplements at least 1 day/week, occasional consumers (OC) using protein supplement less than once a week, and non-consumers (NC) consuming no protein supplement at all. Results: Almost 31% boys consumed protein supplements at least 1 day/week. There was no significant difference in overall energy intake but PC had higher protein intake than NC and OC (2.1±1.0 vs. 1.5±0.6g/kg and 1.8±0.7, p=0.001). PC got significantly more vitamins from their diet than NC and OC. PC consumed more skyr than NC (129 g vs 44 g) but less than OC (154 g/d), p=0.013 like, PC they consumed more protein supplements than OC (350 g/day vs. 29 g/day), p<0.001. Significantly more PC felt they needed more nutrition knowledge than NC (p=0.026). PC and OC counted more on friends as a source of knowledge than NC (p=0.030), whose parents were their greatest knowledge source, compared to PC (p=0.042). More PC claimed they tried to eat healthier than NC and OC, ...